Participatory Action Research in Developing the Instructional Media by Integrating Local Wisdom with the Ways of Life in Local Communities - แสนใจพรม, สายฝน (Community and Social Development Journal, 2016)
The aim for this research was to study the participation of community and investigate the effects of facilitating participatory action research to develop the instructional media by means of integrating local wisdom in accordance with ways of life in local communities in Doisaket district, Chiang Mai province. The research instruments were observation, questionnaire, and brainstorming guidelines question. Qualitative data was analyzed using content analysis. The research findings were summarized as follows : 1. The participation of the communities involved brainstorming, providing local wisdom data, creating and criticizing the media based on learning management. The participation of the two educational institutions involved creating and implementing the media. The participation of the university involved creating, supervising, and monitoring all the processes in order to achieve the goal. 2. From conducting the research, the two sets of media were created in accordance with the contexts and ways of life in local communities. The first set was produced in the aspect of ancient rice farming available in the area of Banrongkheelek community. The second one was made in the aspect of Tai Lue ways of life. 3. New generations pride in their own local wisdom. The local wisdom have been preserved and continue to learn from the instructional media.